Speciation of arsenic in vegetables and their correlation with inorganic phosphate level - Jahanara Laizu (Bangladesh Pharmacological Society, 2007)
A total 400 vegetable sample of 20 varieties of three categories were collected from a local market of Dhaka city. Speciation of arsenic (inorganic arsenic, MMA and DMM) and the amount of inorganic phosphate were estimated. There is no significant variation in the concentrations of inorganic phosphate levels amoung the three categories of vegetables. But in case of arsenic accumulation the fruiting vegetables, root and tuber vegetables and leafy vegetables showed significant variation. There is either positive or negative relationship present in inorganic phosphate and speciated arsenic among the vegetables. Significant negative relationship between inorganic phosphate and inorganic arsenic is observed in different types of fruiting vegetables e.g., bitter ground, tomato, between inorganic phosphate and DMA in bitter gourd, and between inorganic phosphate and total arsenic in bitter gourd, lady's finger, and tomato. The fruiting vegetables contain low level of arsenic, which might have some relationship with higher level of inorganic phosphate. In root and tuber vegetables, significant relationship was present in arum. But in case of arum loti significant positive relationship is observed between inorganic phosphate and DMA. The present study shows that the leafy vegetables contain higher level of inorganic phosphate in contrast to arsenic, though they had no significant relationship between inorganic phosphate and different speciated form of arsenic.